A Multicenter Study of Acute Abdomen in Children With Acute Lymphoblastic Leukemia: CCCG‐ALL‐2015 - Wenting Gan; Weina Zhang; Jiaoyang Cai; Xiaofan Zhu; Jie Yu; Peifang Xiao; Ju Gao; Yongjun Fang; Changda Liang; Xue Li; Fen Zhou; Xiaowen Zhai; et al. (Cancer Medicine)
ABSTRACT Objective Acute abdomen presents a significant challenge in the treatment of childhood acute lymphoblastic leukemia (ALL), potentially leading to treatment failure and treatment‐related mortality. Results from the multicenter study of CCCG‐ALL‐2015 showed significant improvements in overall survival (OS) and event‐free survival (EFS) for childhood ALL. However, the primary aim of this study was to determine the incidence, risk factors, and clinical impact of acute abdomen in the CCCG‐ALL‐2015 protocol, with the ultimate goal in the future of establishing evidence‐based preventive strategies to reduce its occurrence. Methods Patients participating in the CCCG‐ALL‐2015 protocol from January 1, 2015, to December 31, 2019, were included in this analysis. The occurrence of acute abdomen in 7640 patients with ALL was analyzed retrospectively. The data was collected in August 2023 from the Data Center. Acute abdomen analyzed in this study included: acute pancreatitis, acute appendicitis, ileus, enterobrosis, enterorrhagia, peritonitis, enteritis, and others (urinary calculus, anaphylactoid purpura, cholecystitis). The clinical data of patients with acute abdomen were extracted from the database and analyzed. Results A total of 7640 patients were recruited in the study, and 512 (6.7%) patients diagnosed with acute abdomen were identified. Of the 512 patients, 50 patients experienced two episodes of acute abdomen, 5 patients had three episodes, and 2 patients had four episodes. Among different types of acute abdomen, the incidence of acute pancreatitis was the highest (4.0%), followed by ileus (1.2%) and acute appendicitis (0.7%). There was no difference in the incidence of acute abdomen between males and females (6.6% vs. 6.9%, p = 0.64). The incidence of acute abdomen was associated with age, and patients older than 10 years had a significantly higher incidence rate than those less than 1 year and 1–10 years old (13.0% vs. 5.7%, p < 0.0001). The incidence rate of enterorrhagia was significantly higher in patients less than 1 year and older than 10 years than that in patients aged 1–10 years old (1.4% vs. 0.4%, p < 0.0001). The incidence of acute abdomen in the intermediate or high‐risk (I/HR) group was higher than that in the low‐risk (LR) group (9.9% vs. 3.7%, p < 0.001). Acute abdomen mainly occurred in the induction remission phase (57.3%) and the continuation and reinduction phase (39.3%). A total of 16 patients died from acute abdomen, including four patients in the LR group and 12 patients in the I/HR group. Among the different types of acute abdomen, the mortality rate of enterorrhagia was the highest (16.7%), followed by enterobrosis (9.1%). Conclusion This multicenter study investigates the frequency, risk factors, and impact of acute abdomen in the CCCG‐ALL‐2015 protocol, the largest pediatric ALL study in China. We identified acute abdomen in 6.7% of patients, with the highest incidence during the induction remission phase and in older children and those with intermediate or high‐risk ALL. Acute pancreatitis was the most common type, while enterorrhagia had the highest mortality. These findings underscore the need for heightened vigilance and proactive management of acute abdomen to improve outcomes in children with ALL. Trial Registration Chinese Clinical Trial Registry: ChiCTR‐IPR‐14005706